The Attitude of Help-Seeking Behavior Preventing from Mental Health Problems among Adolescents Living in District of Bondowoso - Nandy Agustin Syakarofath; Dian Caesaria Widyasari (UIN Sunan Kalijaga, 2023)
The onset of mental health problems during adolescence often manifests into internalizing and externalizing problems. Seeking help to deal with mental health problems suggested better well-being outcomes. This study investigated the contribution of attitude and intention of seeking help for mental health problems among adolescents. Further analysis examined preferences of formal and informal mental health providers and gender-related patterns on help-seeking behaviors and mental health problems among adolescents. A total of 300 adolescents based on multistage random sampling (mean age = 16.49, male = 131 (43.7%), female = 169 (56.3%)) were selected to participate in this study. They completed three questionnaires online, including The Strengths and Difficulties Questionnaire (SDQ), Mental Help Seeking Intention Scale (MHSIS) and Mental Help-Seeking Attitudes Scale (MHSAS). The results showed that attitude to help-seeking contributes significantly to adolescents internalizing and externalizing problems. Female adolescents were more susceptible to experiencing internalizing and externalizing problems. They showed a more positive attitude and stronger intention to seek mental health assistance than their male counterparts. Finally, teachers and friends are the preferred sources of help in dealing with mental health problems. Munculnya masalah kesehatan mental pada masa remaja seringkali bermanifestasi menjadi masalah internalisasi dan eksternalisasi. Mencari bantuan untuk menangani masalah kesehatan mental menunjukkan hasil kesejahteraan yang lebih baik. Penelitian ini menyelidiki kontribusi sikap dan niat mencari bantuan untuk masalah kesehatan mental di kalangan remaja. Analisis lebih lanjut memeriksa preferensi penyedia kesehatan mental formal dan informal dan pola terkait gender pada perilaku mencari bantuan dan masalah kesehatan mental di kalangan remaja. Sebanyak 300 remaja berdasarkan multistage random sampling (usia rata-rata = 16,49, laki-laki = 131 (43,7%), perempuan = 169 (56,3%)) dipilih untuk berpartisipasi dalam penelitian ini. Mereka mengisi tiga kuesioner online, termasuk Kuesioner Kekuatan dan Kesulitan (SDQ), Skala Niat Mencari Bantuan Mental (MHSIS) dan Skala Sikap Mencari Bantuan Mental (MHSAS). Hasil penelitian menunjukkan bahwa sikap mencari pertolongan berkontribusi secara signifikan terhadap internalisasi dan eksternalisasi masalah remaja. Remaja putri lebih rentan mengalami masalah internalisasi dan eksternalisasi. Mereka menunjukkan sikap yang lebih positif dan niat yang lebih kuat untuk mencari bantuan kesehatan mental daripada rekan pria mereka. Terakhir, guru dan teman adalah sumber bantuan yang lebih disukai dalam menangani masalah kesehatan mental.